Revitalization of local cultural values through etnosport-based teaching materials to enhance students’ character - Mariamah Mariamah; Muhamad Muhamad; Subhan Subhan; Firdaus Firdaus; Salahudin Salahudin (Research and Social Study Institute, 2026)
This study aims to develop an Etnosport-based Physical Education, Sports, and Health (PJOK) textbook to enhance the character and creativity of Phase F students at SMA Negeri 1 Palibelo. The research employed a research and development approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The trial subjects consisted of 25 students and 2 PJOK teachers. Research instruments included questionnaires, tests, interviews, and observations, validated by subject matter experts, language experts, and media experts. The validation results indicated that the textbook was rated “Excellent” in the material aspect (94–96%), “Excellent” in the language aspect (90–95%), and “Good” in the appearance aspect (81–83%). Field trials showed that students and teachers rated the practicality of the textbook as “Excellent” (≥ 92.5%). The implementation of Etnosport-based learning had a positive impact on students’ character, with 84% of students falling into the “Excellent” category and an N-gain of 0.83 (high category). The developed textbook proved effective in instilling values of discipline, responsibility, cooperation, sportsmanship, independence, self-confidence, and respect through contextual, engaging, and culturally based learning.